Moving towards ambitious climate policies: Monetised health benefits from improved air quality could offset mitigation costs in Europe. Issue 50 (June 2015) - Schucht, Simone; Colette, Augustin; Rao, Shilpa; Holland, Mike; Schöpp, Wolfgang; Kolp, Peter; Klimont, Zbigniew; Bessagnet, Bertrand; Szopa, Sophie; Vautard, Robert; Brignon, Jean-Marc; Rouïl, Laurence
Highlights: Climate policies generate co-benefits for air pollution. Co-benefits from ambitious climate policy offset a large part of mitigation costs. Current European air pollution policy effectively reduces total health damage. Emission reductions in Europe dominate reductions in PM2.5 related health impacts. Reducing health impacts from ozone requires ambitious international climate policy. Abstract: Air quality and related health effects are not only affected by policies directly addressed at air pollution but also by other environmental strategies such as climate mitigation. This study addresses how different climate policy pathways indirectly bear upon air pollution in terms of improved human health in Europe. To this end, we put in perspective mitigation costs and monetised health benefits of reducing PM2.5 (particles less than 2.5 μm in diameter) and ozone concentrations. Air quality in Europe and related health impacts were assessed using a comprehensive modelling chain, based on global and regional climate and chemistry-transport models together with a health impact assessment tool. This allows capturing both the impact of climate policy on emissions of air pollutants and the geophysical impact of climate change on air quality. Results are presented for projections at the 2050 horizon, for a set of consistent air pollution and climate policy scenarios, combined with population data from the UN's World Population Prospects, and are expressed in terms of morbidity and mortality impacts of PM2.5 and ozone pollution and their monetised damage equivalent. The analysis shows that enforcement of current European air quality policies would effectively reduce health impacts from PM2.5 in Europe even in the absence of climate policies (life years lost from the exposure to PM2.5 decrease by 78% between 2005 and 2050 in the reference scenario), while impacts for ozone depend on the ambition level of international climate policies. A move towards stringent climate policies on a global scale, in addition to limiting global warming, creates co-benefits in terms of reduced health impacts (68% decrease in life years lost from the exposure to PM2.5 and 85% decrease in premature deaths from ozone in 2050 in the mitigation scenario relative to the reference scenario) and air pollution cost savings (77%) in Europe. These co-benefits are found to offset at least 85% of the additional cost of climate policy in this region.